Olive by-products for functional and food applications: Challenging opportunities to face environmental constraints. (June 2016) - Nunes, M. Antónia; Pimentel, Filipa B.; Costa, Anabela S.G.; Alves, Rita C.; Oliveira, M. Beatriz P.P.
Abstract: This comprehensive review points out the major developments on the recovery of bioactive compounds of olive by-products, intending innovative food applications and enhanced technological functions. Nutritional and sensorial factors influencing consumers' acceptance are also discussed. Besides being an economic burden for producers, olive oil by-products also represent a severe environmental problem. Simultaneously, these are rich in bioactive compounds, which are remarkable added-value ingredients for other industries. New applications have been focused in ameliorating the food nutritional profile, replacing or improving technological properties/functions of food additives, and extending food products shelf life. Eco-friendly food packaging is also a promissory application field. The improvement of nutritional functionality and sensory quality of enriched food is another challenging task. Despite the large chemical characterization of olive products and olive oil processing by-products, further research is still needed to fully understand the potential of this valuable raw material. Industrial relevance: High added-value ingredients can be obtained by recovering bioactive compounds from olive by-products. Those can be used by food industry to improve food product nutritional profile and/or with a technological functionality. This review presents food applications developed with ingredients and bioactive compounds derived from olive processing by-products. It aims to be useful for food industries and other agro-industrial stakeholders in order to encourage and expand the utilization of olive by-products in the development of innovative food products. Highlights: There has been a great by-products generation with the growth of olive oil production. Olive by-products have high content in bioactive compounds. Olive by-products have high potential to be used in food applications. Food functional properties are improved using olive by-products as ingredients. Food technological properties are improved using olive by-products as ingredients.